2014
DOI: 10.1097/mpa.0000000000000236
|View full text |Cite
|
Sign up to set email alerts
|

Total Pancreatectomy With Islet Autotransplantation

Abstract: A workshop sponsored by the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) focused on research gaps and opportunities in total pancreatectomy with islet autotransplantation (TPIAT) for the management of chronic pancreatitis (CP). The session was held on July 23, 2014 and structured into five sessions: (1) patient selection, indications, and timing; (2) technical aspects of TPIAT; (3) improving success of islet autotransplantation; (4) improving outcomes after total pancreatectomy; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…These findings build upon previously reports of relationship between MRI findings and islet yield [9], are clinically applicable to counseling the TPIAT recipient, and address an important research gap recently identified by experts in the field of TPIAT, to better define markers for diabetes risk after TPIAT [18]. Calcifications in particular increased the odds of insulin dependence greatly—those with parenchymal calcifications were at 4 fold greater risk of remaining insulin dependent at 1 year after the surgery compared to those without.…”
Section: Discussionsupporting
confidence: 73%
“…These findings build upon previously reports of relationship between MRI findings and islet yield [9], are clinically applicable to counseling the TPIAT recipient, and address an important research gap recently identified by experts in the field of TPIAT, to better define markers for diabetes risk after TPIAT [18]. Calcifications in particular increased the odds of insulin dependence greatly—those with parenchymal calcifications were at 4 fold greater risk of remaining insulin dependent at 1 year after the surgery compared to those without.…”
Section: Discussionsupporting
confidence: 73%
“…For many years, TP with pancreatic transplantation has been conducted in patients with type 1 diabetes[ 119 ] and TP combined with islet autotransplantation has been performed on chronic pancreatitis patients with intractable pain[ 121 ]. However, most recently, due to the improvements in post-surgical quality of life, these treatment procedures have been considered and actually indicated for FPC kindred with premalignant lesions[ 119 , 122 , 123 ].…”
Section: Surveillance Of High Risk Individualsmentioning
confidence: 99%
“…Reduction in pain and narcotic dependence after pancreatectomy, as well as maintenance of islet cell function after autotransplantation, have only been shown to be moderately successful, as well as age dependent, being more successful in younger patients. 100 , 101 Pancreatectomy with islet cell autotransplantation is an irreversible procedure with rare but serious risks and commits the patient to a lifetime of exogenous pancreatic enzyme replacement as well as a high likelihood of insulin dependence over time. Thus, extensive risk–benefit analysis by a multidisciplinary team, which is individualized to the patient, needs to be undertaken prior to the decision to pursue surgical resection.…”
Section: Treatmentmentioning
confidence: 99%